2006
DOI: 10.1007/s10495-006-5877-5
|View full text |Cite
|
Sign up to set email alerts
|

Indole-3-carbinol-induced death in cancer cells involves EGFR downregulation and is exacerbated in a 3D environment

Abstract: (211 words)Indole-3-carbinol (I3C) is a promising anticancer dietary compound, which inhibits breast cancer in animal models. The objective of the current study was to characterize I3C-induced cells using an EGFR inhibitor resulted in apoptosis. EGFR modulation using EGF or an EGFR inhibitor markedly influenced viability and response to I3C in MDA-MB-468 cells in 3D conditions. EGFR expression was modulated by 3D conditions. Therefore, I3C-induced EGFR reduction in these cells is likely to be responsible for I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 40 publications
(30 reference statements)
1
16
0
2
Order By: Relevance
“…It was encouraging to note that EGFR was downregulated by I3C in the present study as observed in response to single high doses (8,9). I3C-induced reduction in vimentin was not related to decreased EGFR signaling (Fig.…”
Section: Physiological Activities Of Dietary Agentssupporting
confidence: 69%
See 2 more Smart Citations
“…It was encouraging to note that EGFR was downregulated by I3C in the present study as observed in response to single high doses (8,9). I3C-induced reduction in vimentin was not related to decreased EGFR signaling (Fig.…”
Section: Physiological Activities Of Dietary Agentssupporting
confidence: 69%
“…Our previous studies showed that treatment of MDA-MB-231 cells with 250 Amol/L I3C decreased protein levels of EGFR, cyclin D1, and cyclin-dependent kinase 6, whereas p21Cip1, p27Kip1, and cyclin E were increased (8). We also showed that I3C-induced apoptosis is related to down-regulation of EGFR in these cells (8,9). The latter is consistent with the data obtained in this model because reduced EGFR signaling in combination with diluted autocrine transforming growth factor-a is bound to increase apoptosis and reduce growth in clonogenic assay.…”
Section: Physiological Activities Of Dietary Agentsmentioning
confidence: 75%
See 1 more Smart Citation
“…Other studies indicated that I3C down regulated epidermal growth factor receptor (EGFR) in human breast cancer cell lines and induce cell cycle arrest and apoptosis [51,52]. In addition, it was shown that DIM treatment induced hyperpolarization of mitochondrial inner membrane, decreased cellular ATP level, and significantly stimulated mitochondrial reactive oxygen species (ROS) production.…”
Section: The Anti-cancer Effect Of Indole-diet Derivatives the Effectmentioning
confidence: 99%
“…Although fairly high concentrations of some phytochemicals are appropriate in cells from tissues with high bioavailability (e.g., liver for I3C and DIM or colon for curcumin and EGCG), lower concentrations should be used for cells from tissues dependent on systemic bioavailability. Physiologically unrealistic concentrations have been used in many studies, including some of our own, to increase or hasten detection of end points (73,82,90 (90,91). Recent studies in breast cancer cells using EGCG (40-160 μg/mL = 87-351 μmol/L, which is borderline or toxic for normal breast cells) indicate that FOXO3 is involved in EGCG-induced cell death, reduced invasiveness, increased expression of E-cadherin and ERα, whereas further work from the same group suggests that EGCG may modulate E-cadherin expression via downregulation of CK2 and c-Rel signaling (92)(93)(94).…”
mentioning
confidence: 99%